Correlation between Knowledge, Preventive Behaviors, and COVID-19 Anxiety with Perceived Stress among Pregnant Women: A Cross-sectional Study. - Aalaei, Maedeh; Abbasalizadeh, Fatemeh; Sarvaran, Kosar; Kazemi, Azita Fathnezhad (Journal of Midwifery & Reproductive Health, 2024)
Background & aim: Psychological and behavioral factors caused by COVID-19 adversely affect physical and mental well-being, especially in pregnant women. The current study was performed to evaluate the correlation between knowledge, preventive behaviors, and COVID-19 anxiety with perceived stress among pregnant women. Methods: This cross-sectional study was conducted among 290 pregnant women referring to two hospitals in Tabriz, Iran in the second six months of 2021. All participants were selected through convenient sampling. Data were collected using demographic-obstetric questionnaire, knowledge of COVID-19 questionnaire, preventive behaviors scale against COVID-19, the Corona Disease Anxiety Scale (CDAS), and the Cohen Perceived Stress Scale (PSS). Data were analyzed by SPSS software version 24 and descriptive and interpretive statistics. Results: Based on the results, 23.8% and 38.6% of participants had severe anxiety and stress, respectively. There was a direct and significant correlation between knowledge and preventive behaviors (r=0426, P<0.001). The results of univariate regression showed that the preventive behaviors and COVID-19 anxiety explain 1.7% (β=0.130, SE=0.123, P=0.027) and 5.51% (β=0.742, SE=0.034, P<0.001) of stress changes, respectively. In univariate linear regression, a moderate correlation was observed between the three variables including employment status, preventive behaviors, and anxiety with perceived stress (R=0.557), and anxiety had the highest regression coefficient (β=-0.665). Conclusion: The current study highlighted the importance of measuring knowledge, preventive behaviors, COVID- 19 anxiety and perceived stress in pregnant women during COVID-19 pandemic. This assessment will assist healthcare providers in delivering appropriate services during the future pandemics.